Identification of immune subtypes associated with the prognosis in skull base chordoma - Yujia Xiong; Mingxuan Li; Guangyi Niu; Tianyi Xu; Chuzhong Li; Tianshun Ma; Tianhao Zhang; Hela Koka; Lili Hao; Yazhuo Zhang; Jiwei Bai; Xiaohong R. Yang (Acta Neuropathologica Communications)
Abstract Chordoma is a rare malignant bone tumor that is prone to local recurrence. Recent omics studies suggest that chordoma is a heterogenous disease and the tumor immune microenvironment (TIME) may be associated with chordoma recurrence and patient survival. The aim of this study was to explore the prognostic role of TIME in skull base chordoma. We conducted RNA sequencing of fresh frozen tumors from 77 Chinese skull base chordoma patients and performed unsupervised clustering using immune cell scores estimated by single sample gene set enrichment analysis (ssGSEA) to identify potential immune subtypes. Immunohistochemical (IHC) staining, ESTIMATE, CIBERSORT and xCell were used to validate differences in immune composition between the two immune subtypes. An independent cohort of 261 skull base chordoma patients with long follow-up data was further used to investigate the prognostic associations of immune cells. We identified two immune subtypes (A and B) of skull base chordoma. Compared to tumors in cluster A, tumors in cluster B had higher infiltration of most immune cell populations especially macrophages and T cells. The differences were confirmed by IHC staining of CD68, CD163, and CD3 in a subset of patients (n = 51) with fixed tumor blocks available. Moreover, higher proportions of macrophages (CD68 and CD163) were significantly correlated with shorter PFS (CD68: P < 0.001, CD163: P < 0.001) and OS (CD68: P = 0.04, CD163: P = 0.004) in an independent set of 261 patients with long follow-up data. Our study identified immune subtypes of chordoma that were associated with clinical outcomes and highlighted the potential prognostic value of macrophages. These findings may enhance our understanding of TIME and suggest the importance of macrophages in chordomas.